Wet-Chemical Surface Texturing of Sputter-Deposited ZnO:Al Films as Front Electrode for Thin-Film Silicon Solar Cells - Xia Yan; Selvaraj Venkataraj; Armin G. Aberle (International Journal of Photoenergy)
Transparent conductive oxides (TCOs) play a major role as the front electrodes of thin-film silicon (Si) solar cells, as they can provide optical scattering and hence improved photon absorption inside the devices. In this paper we report on the surface texturing of aluminium-doped zinc oxide (ZnO:Al or AZO) films for improved light trapping in thin-film Si solar cells. The AZO films are deposited onto soda-lime glass sheets via pulsed DC magnetron sputtering. Several promising AZO texturing methods are investigated using diluted hydrochloric (HCl) and hydrofluoric acid (HF), through a two-step etching process. The developed texturing procedure combines the advantages of the HCl-induced craters and the smaller and jagged—but laterally more uniform—features created by HF etching. In the two-step process, the second etching step further enhances the optical haze, while simultaneously improving the uniformity of the texture features created by the HCl etch. The resulting AZO films show large haze values of above 40%, good scattering into large angles, and a surface angle distribution that is centred at around 30°, which is known from the literature to provide efficient light trapping for thin-film Si solar cells.